Hábitos alimentarios, estrés académico y estado nutricional en los estudiantes de la Facultad de Farmacia y Bioquímica de la Universidad Nacional de la Amazonía Peruana - Iquitos, 2024 - Lancha Pizango, Zenaida (2024)
The objective of this study was to determine the relationship between eating habits and academic stress with the nutritional status of students from the Faculty of Pharmacy and Biochemistry of the National University of the Peruvian Amazon. The study had a descriptive and correlational approach, not an experimental, cross-sectional quantitative approach. Sampling was non probabilistic for convenience. The stucco sample was made up of 100 second to fifth level. Nutritional evaluation was carried out and questionnaires were filled out. 49% had a normal body mass index, 35.00% were overweight, 14% had grade I obesity, 1.00% had grade II obesity and thinness. 59.00% presented an abdominal perimeter without risk, 36.00% had high risk and 5.00% had very high risk. 22.00% had optimal body fat, 6.00% had low-high body fat, 18.00% had moderate body fat, 28% had high body fat and 26.00% had very high body fat. With respect to hemoglobin, 65% of students had a normal state, 28.00% had mild anemia, 6% had moderate anemia and 1.00% had severe anemia. 89.00% had normal glucose, 10.00% had low glucose and 1.00% had high glucose. 65.00% had bad or unhealthy eating habits, 35.00% had regular eating habits or needed changes and none had good or healthy eating habits and 7.00% had very high academic stress, 51.00% very high, 41.00% medium and 1.00% very low. It was concluded that there is a statistical relationship between eating habits and academic stress and its indicators with body mass index, abdominal perimeter, anemia and body fat, but not with blood glucose.